Effect the addition of Anis seed(Pimpinella anisum L.) powder on production performance and some blood and biochemical parameters in broiler chickens - Zahira A. AL-Zuhairi; Afrah S. AL-Tabari (Kufa Journal for Veterinary Medical Sciences, 2013)
This study was conducted at commercial farm for broiler which is located in Diwaniya city,from 1/4/2013 to 20/5/2013 to estimate the effect supplementation of two concentration of Anis seeds powder to feed  on production performance and some blood traits and blood biochemical parameters of broiler chickens by using (150) broiler chicken (Hubbard) at one day old which have been randomly distributed to three treatments by two replication per treatment(25 chicks per replication),this chicks divided into  the following: